ANALYSIS OF RISK FACTORS FOR THE INCIDENT OF EARLY ONWARD NEONATAL SEPSIS REVIEWED FROM THE APGAR SCORES AND WEIGHT AT BIRTH AT KUDUNGGA HOSPITAL - Eri Puji Kumalasari; Devy Putri Nursanti; Poni Angelia (Journal for Quality in Women's Health, 2024)
Neonatal sepsis is one of the most common causes of death in neonates.. The aim of this study was to analyze the relationship between early onset neonatal sepsis in terms of the score. APGAR and birth weight infants. The research design used was correlational analytic with a cross sectional time approach with a total sample of 52 respondents. The sampling method in this study used the Accidental Sampling technique. Data were collected using medical record data .Test the analysis using the Chi Square Test. The APGAR score in newborns is known to be mostly in the APGAR score category 7-10 (no asphyxia) (73.1%). Almost all of the birth weights of newborns were found to be in the birth weight category ≥2500 grams (77%). The incidence of early-onset neonatal sepsis in newborns is known to be mostly in the category of no early-onset neonatal sepsis (69.2%).